Pengaruh Penyalahgunaan Teknologi Informasi, Integritas Mahasiswa dan Motivasi Belajar terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi - Dewandaru Agung Pramita; Bambang Subiyanto; Danang Aryo Wicaksono (Syntax Corporation, 2022)
The purpose ofithis study wasito testithe empirical andithe effect ofiInformation Technology misapproproate, Integrity, and Learn Motivation Against Fraudulent Behavior Accounting Student Academic (Study oniaccounting study program economic and business faculty national university academic year 2021 - 2022). The object in this study was the Accounting Students at the National University of 2018 – 2020, the sample in this study was 125 respondents. The data obtained are primary data from the results of the questionnare. The data testing method used is descriptive statistical test, data quality tes, classical assumption test, multiple linear regression analysis and hypothesis testing using SPSS version 26.0. The results ofithis study indicateithat information technologyihas a positiv ieffect on violation behavior, integrity has a positive effec ion academic violationibehavior and learningimotivation has ainegative effect oniacademic behavior.